Oscillation and nonoscillation criteria for a half-linear difference equation of the second order and extended discrete Hardy inequality - Kalybay, A.; Karatayeva, D. (Ukrains’kyi Matematychnyi Zhurnal, 2022)
UDC 517.9 We establish the oscillatory properties of a half-linear difference equation of the second order by using a suitable extension of the weighted discrete Hardy inequality.